A Gynecologic Oncology Group Study of serum CA-125 levels in patients with stage III optimally debulked ovarian cancer treated with intraperitoneal compared to intravenous chemotherapy: An analysis of patients enrolled in GOG 172 - Krivak, Thomas C. (Gynecol Oncol, 2009)
OBJECTIVE: Serum CA-125 values have been advocated in the monitoring of ovarian cancer patients receiving intravenous (IV) chemotherapy. This evaluation sought to determine if the CA-125 test can be used to monitor treatment effect among patients receiving intraperitoneal chemotherapy (IP). METHODS: Patient charts from a phase III clinical trial (GOG 172) were retrospectively reviewed. Serum CA-125 levels prior to each cycle of therapy were collected and compared between the IV and IP chemotherapy delivery. The association between CA-125 and progression-free survival (PFS) or overall survival (OS) was estimated and the homogeneity of the results between IP and IV chemotherapy was assessed. RESULTS: A total of 177 patients were treated with IV chemotherapy and 165 patients with IP chemotherapy with CA-125 data available were included in this analysis. The observed difference was not statistically significant in median CA-125 levels between the IV and IP arms at any time point (P>0.05 for all). Following surgery and adjuvant chemotherapy, patients with an abnormal CA-125 >35 U/ml were 2.45 times more likely to have disease progression (95% CI: 1.52–3.95, P<0.001) and 2.78 times more likely to die of disease (95% CI: 1.66–4.65, P<0.001), compared to those with a CA-125 <35 U/ml. These results were consistent with IP and IV chemotherapy. CONCLUSION: Serum CA-125 levels decrease in a similar manner during IP chemotherapy when compared to IV chemotherapy. Serum CA-125 algorithms for monitoring treatment effect that have been established for IV chemotherapy may also be applied for patients receiving IP chemotherapy.